Acceso a la educación para mujeres en prisión: la educación en prisión desde la perspectiva de género - da Silva Cardoso, Fernando; Bomfim, Alanna (Educar Mais, 2022)
This research aims to discuss how the right to education is guaranteed when it comes to the reality of imprisoned women. From a gender perspective and perspective, the legal and educational scenario that protect this right is read from a gendered perspective as a way to discuss the gaps that undermine the guarantee of the right to education for that public. Qualitative in nature, and instrumentalized from a literature review, the study highlights some of the gender issues that are involved with access to education by women prisoners, as well as the social conditions surrounding them and the provision of education in prison. . The findings point to the disparities that involve the reality experienced in prison, the lack of professionals in the field of education, aspects related to architecture, vacancies and disrespect for the uniqueness of women prisoners. Finally, we argue that there is a given invisibility, perpetuated by the State, with regard to educational issues in prison and the break with gender stereotypes that, in general, make difficult the unique guarantee of the right to education for women prisoners.